Empowerment of Class IIA Prison Jember in Participatory Actions to Achieve Pulmonary Tuberculosis Elimination by 2030 - Frisca Florensia; Indah Sukma Wahyuni; Rini Tri Astutik; Kurniawan, Hendra; Handayani, Luh Titi (Jurnal Pengabdian Masyarakat (JUDIMAS), 2023)
The World Health Organization (WHO) estimates that Mycobacterium tuberculosis, the single agent causing pulmonary tuberculosis (TB), infects 1.8 billion people, or around one-quarter of the world's total population. In Indonesia, there are an estimated 969,000 cases of pulmonary TB, including 443,235 reported cases. Prison is a high transmission site for pulmonary TB. Prison circumstances, such as high occupancy capacity, inadequate ventilation and nutrition, difficulties accessing health care, inadequate treatment, and weak patient immunity, are some of the variables influencing this. Knowledge on the origins, transmission, preventative strategies, and early diagnosis of pulmonary TB infection is essential for the prisoner in order to change attitudes toward pulmonary TB infection. This Community Service Program intends to expand the prisoner's knowledge about pulmonary TB via 3 stages including preparation, implementation, and evaluation. The target of this program is 47 male prisoners in the Prison of Jember Class IIA. The findings were evaluated after delivering pulmonary TB counseling materials (post test) and revealed an increase in the mean value to 79.6, implying that prisoner's awareness of pulmonary TB increased.